The Human Likeness Dimension of the “Uncanny Valley Hypothesis”: Behavioral and Functional MRI Findings - Cheetham, Marcus; Suter, Pascal; Jäncke, Lutz (Frontiers in Human Neuroscience, 2011)
The uncanny valley hypothesis (Mori, 1970) predicts differential experience of negative and positive affect as a function of human likeness. Affective experience of realistic humanlike robots and computer-generated characters (avatars) dominates “uncanny” research, but findings are inconsistent. How objects are actually perceived along the hypothesis’ dimension of human likeness (DOH), defined only in terms of human physical similarity, is unknown. To examine whether the DOH can be defined also in terms of effects of categorical perception (CP), stimuli from morph continua with controlled differences in physical human likeness between avatar and human faces as endpoints were presented. Two behavioural studies found a sharp category boundary along the DOH and enhanced visual discrimination (i.e. CP) of fine-grained differences between face pairs at the category boundary. Discrimination was better for face pairs that presented category change in the human-to-avatar than avatar-to-human direction along DOH. To investigate brain representation of physical and category change within the uncanny valley hypothesis’ framework, an event-related fMRI study used the same stimuli in a paired repetition-priming paradigm. Bilateral mid-fusiform areas and a different right mid-fusiform area were sensitive to physical change within the human and avatar categories, respectively, whereas entirely different regions were sensitive to the human-to-avatar (caudate head, putamen, thalamus, red nucleus) and avatar-to-human (hippocampus, amygdala, mid-insula) direction of category change. Our findings show that Mori's DOH definition does not reflect subjective perception of human likeness and suggest that future “uncanny” studies consider CP and the DOH category structure in guiding experience of nonhuman objects.